2016
DOI: 10.1101/058610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AtypicalSalmonella entericaserovars in murine and human infection models: Is it time to reassess our approach to the study of salmonellosis?

Abstract: Nontyphoidal Salmonella species are globally disseminated pathogens and the predominant cause of gastroenteritis. The pathogenesis of salmonellosis has been extensively studied using in vivo murine models and cell lines typically challenged with Salmonella Typhimurium. Although serovars Enteritidis and Typhimurium are responsible for the most of human infections reported to the CDC, several other serovars also contribute to clinical cases of salmonellosis. Despite their epidemiological importance, little is kn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Several studies have reported that S. enterica serovar Typhimurium and other S. enterica serovars which grow as yellow colonies on XLD agar [72,73]. Out of the 195 colonies that grew on the presumptive XLD agar, only 35 were red with black centers while 160 colonies were yellow pigmented, and some with black centers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that S. enterica serovar Typhimurium and other S. enterica serovars which grow as yellow colonies on XLD agar [72,73]. Out of the 195 colonies that grew on the presumptive XLD agar, only 35 were red with black centers while 160 colonies were yellow pigmented, and some with black centers.…”
Section: Discussionmentioning
confidence: 99%
“…These primers were designed from the highly conserved sequences across all strain-specific regions in their reference genomes like STY0307 genes for S. Typhi and an intergenic region between SSPA1723a and SSPA1724 for S. Paratyphi A. Many studies have examined thousands of Salmonella genomes that are accessible and have discovered SNPs that are unique to particular lineages [32,[34][35][36]. In several South Asian nations, the predominant strain of S. Typhi is genotype 4.3.1 (H58), which is highly resistant to 27 antibiotics [36].…”
Section: Discussionmentioning
confidence: 99%